Neuregulin-1, or NRG 1, is a powerful cardiomyocyte proliferator that impacts the circulatory system. Endothelial cells in the bloodstream secrete and release it. It is essential for the development, proliferation, differentiation, apoptosis, and other ca - Wafaa Sh. Al – Zuhairi Sh. Al – Zuhairi; Leila Sadeghi; Ekhlas Abdallah Hassan (Academic Science Journal)
Abstract